Prediction of velocity at maximum oxygen uptaker in race walkers - Drake, A.; Woolley, R.; Cox, V.; Godfrey, R.; James, R.; Brooks, S. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Athletes regularly compete in race walking events over distances of 3 km, 5 km and 10 km as well as the Olympic distances of 20 km and 50 km. Race walking competition demands that athletes maintain strict technique as determined by the International Amateur Athletic Federation. Predicting laboratory measures of race walking performance from a time trial field test could be useful to athletes and coaches. In sub-elite runners Billat et al. (1994) reported time to exhaustion at the velocity at maximum oxygen uptake (v-VO2max) was 402 ± 113 s, which would represent a similar duration to an all out 2 km performance in a trained race walker. The purpose of this study was to examine the relationship between selected physiological variables identified during laboratory based race walking exercise and a field based 2 km race walking time trial. Thirteen male and eight female athletes from the UK Athletics National Race Walking Squad volunteered for this study, which had University ethical approval. The mean ± SD age, height, body mass and VO2max were 22 ± 9 y; 1.75 ± 0.07 m; 62.3 ± 9.1 kg; and 55.6 ± 8.9 ml.kg- 1.min-1. Subjects completed a discontinuous incremental race walking treadmill test until volitional exhaustion for determination of lactate threshold (Tlac) and maximum oxygen uptake (VO2max). Velocity at lactate threshold (v-Tlac) was identified as the velocity immediately preceding an increase in Blac by 1.0 mmol.l-1 or more above baseline. VVO2max was resolved by linear regression on sub-maximal race walking velocity and VO2 values. Within 24 hours subjects walked an all out 2 km race walking time trial on a 400 m Mondo surface athletics track. The 2 km time trial performance time was 554 ± 65 s. V-2 km was compared to v-VO2max and race walk competition performances over 3 km, 5 km and 10 km recorded within four weeks pre- or post-laboratory test. V-2 km (13.2 ± 1.6 km.h-1) was 0.2 % higher than v-VO2max (13.1 ± 1.5 km.h-1) (p > 0.05); and 10.9 % higher than v-Tlac (11.7 ± 0.7 km.h-1) (p < 0.05). V-VO2max accounted for 94 % of the variance in 2 km time trial performance when analysed by multiple stepwise linear regression. In relation to competition performances v-2 km was 0.3 % higher than v-3 km (p > 0.05); and 4.6 % and 8.4 % higher than v-5 km and v-10 km (p < 0.05). The present study supports the use of a field based 2 km race walking time trial as a predictor of velocity at maximum oxygen uptake and velocity at lactate threshold in race walkers.